Variable Extent of Lineage-Specificity and Developmental Stage-Specificity of Cohesin and CCCTC-Binding Factor Binding Within the Immunoglobulin and T Cell Receptor Loci - Loguercio, Salvatore; Barajas-Mora, E. Mauricio; Shih, Han-Yu; Krangel, Michael S.; Feeney, Ann J. (Frontiers in Immunology, 2018)
CTCF is largely responsible for the 3D architecture of the genome through the creation of long-range chromatin loops. Cohesin is hypothesized to be the main driver of these long-range chromatin interactions by the process of loop extrusion. Here we performed ChIP-seq for CTCF and cohesin in 2 stages each of T and B cell differentiation and examined the binding pattern in all 6 antigen receptor (AgR) loci in these lymphocyte progenitors and in mature T and B cells, ES cells and fibroblasts. The 4 large AgR loci have many bound CTCF sites, most of which are only occupied in lymphocytes, while only the CTCF sites at the end of each locus near the enhancers or J genes tend to be bound in non-lymphoid cells also. However, despite the generalized lymphocyte restriction of CTCF binding in AgR loci, the Igκ locus is the only locus that also shows significant lineage-specificity (T vs. B cells) and developmental stage-specificity (pre-B vs. pro-B) in CTCF binding. We show that cohesin binding shows greater lineage- and stage-specificity than CTCF at most AgR loci, providing more specificity to the loops. We also show that the culture of pro-B cells in IL7, a common practice to expand the number of cells before ChIP-seq, results in a CTCF binding pattern resembling pre-B cells, as well as other epigenetic and transcriptional characteristics of pre-B cells. Analysis of the orientation of the CTCF sites show that all sites within the large V portions of the Igh and TCRβ loci have the same orientation. This suggests either a lack of requirement for convergent CTCF sites creating loops, or indicates an absence of any loops between CTCF sites within the V region portion of those loci but only loops to the convergent sites at the D-J-enhancer end of each locus. The V region portions of the Igκ and TCRα/δ loci, in contrast, have CTCF sites in both orientations, providing many options for creating CTCF-mediated convergent loops throughout the loci. CTCF/cohesin loops, along with transcription factors, drives contraction of AgR loci to facilitate the creation of a diverse repertoire of antibodies and TCRs.